2005
DOI: 10.1177/0075424205285637
|View full text |Cite
|
Sign up to set email alerts
|

Structured Heterogeneity and Change in Laryngeal Phonetics

Abstract: American sociolinguists have largely ignored obstruents as invariant, including how speakers distinguish /s, t/ from /z, d/. Upper Midwestern final obstruents provide clear evidence that the realization of such contrasts can and does vary. In a once German-speaking Wisconsin town, we have found that speakers systematically produce final laryngeal distinctions differently than reported for American English, with an apparent partial neutralization of the distinction. Here, we seek the historical antecedents of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…One of the first questions we use to make sense of new acquaintances is, "Where are you from?" It may have instead increased the need for people to draw boundaries, more crisply define their geographic communities (Bell 1992;Cohen 1985), and perform elements of their identity rooted in physical places, such as speech patterns (Purnell et al 2005). It may have instead increased the need for people to draw boundaries, more crisply define their geographic communities (Bell 1992;Cohen 1985), and perform elements of their identity rooted in physical places, such as speech patterns (Purnell et al 2005).…”
Section: Understanding As Categorization and Social Identificationmentioning
confidence: 99%
“…One of the first questions we use to make sense of new acquaintances is, "Where are you from?" It may have instead increased the need for people to draw boundaries, more crisply define their geographic communities (Bell 1992;Cohen 1985), and perform elements of their identity rooted in physical places, such as speech patterns (Purnell et al 2005). It may have instead increased the need for people to draw boundaries, more crisply define their geographic communities (Bell 1992;Cohen 1985), and perform elements of their identity rooted in physical places, such as speech patterns (Purnell et al 2005).…”
Section: Understanding As Categorization and Social Identificationmentioning
confidence: 99%
“…For instance, in English, in addition to vocal pulsing differences, preceding vowels are ordinarily longer, nearby F 0 can be lowered, nearby F 1 tends to be relatively lower, and the consonantal occlusion may be shorter for a voiced consonant than for a voiceless one. Studies of German–American English in Wisconsin65,66 suggest that dialects can exploit trading relations by manipulating cues. Purnell et al65 showed that in one Wisconsin community, F 0 and F 1 differences were absent in the realization of the [±voice] contrast for syllable‐final stops.…”
Section: Illustrations Of What Language Users ‘Know’mentioning
confidence: 99%
“…However, preceding vowel length and amount of vocal pulsing in the occlusion exhibited a trading relation. Purnell et al66 examined the speech of Wisconsinites born over a 120‐year period and found striking shifts across generations in the cues used for the [±voice] contrast. The oldest generations focused mainly on vocal pulsing in the occlusion and actually showed a reverse relationship for duration of the preceding vowel (vowels averaged slightly longer before voiceless consonants).…”
Section: Illustrations Of What Language Users ‘Know’mentioning
confidence: 99%
“…However, the phenomenon has been documented in, at least, American English, and especially in areas with particularly strong German or other Germanic settlement histories (e.g. Knack 1991 for Grand Rapids, Michigan; Purnell, Salmons and Tepeli 2005; Purnell, Salmons, Tepeli and Mercer 2005 for southeastern Wisconsin, especially Watertown) 7 . Thus, the word bed is variably pronounced very much like the word bet , the word sees is variably pronounced very much like the word cease , and so forth.…”
Section: Introductionmentioning
confidence: 99%